Development of Management Quality Assessment Methodology in the Public Sector: Problems and Contradictions - Kozhevina, Olga Vladimirovna; Yurchenko, Evgeniya Vitalyevna; Balunova, Nataliya Vladimirovna (Economy of Regions, 2015)
The development management quality assessment methodology in the public sector is relevant scientific and practical problem of economic research. The utilization of the results of the assessment on the basis of the authors' methodology allows us to rate the public sector organizations, to justify decisions on the reorganization and privatization, and to monitor changes in the level of the management quality of the public sector organizations. The study determined the place of the quality of the control processes of the public sector organization in the system of “Quality of public administration - the effective operation of the public sector organization,'' the contradictions associated with the assessment of management quality are revealed, the conditions for effective functioning of the public sector organizations are proved, a mechanism of comprehensive assessment and algorithm for constructing and evaluating the control models of management quality are developed, the criteria for assessing the management quality in the public sector organizations, including economic, budgetary, social and public, informational, innovation and institutional criteria are empirically grounded. By utilizing the proposed algorithm, the assessment model of quality management in the public sector organizations, including the financial, economic, social, innovation, informational and institutional indicators is developed. For each indicator of quality management, the coefficients of importance in the management quality assessment model, as well as comprehensive and partial evaluation indicators are determined on the basis of the expert evaluations. The main conclusion of the article is that management quality assessment for the public sector organizations should be based not only on the indicators achieved in the dynamics and utilized for analyzing the effectiveness of management, but also should take into account the reference levels for the values of these parameters. The comparison of the indicators will allow to assess not only the degree of the achievement of objectives and results but also the quality of conformance of the chosen development strategy from a position of management quality.